The Development of Student Digital Worksheets Based on Logan Avenue Problem Solving (LAPS)-Heuristic to Improve Critical Thinking Skills - Yessica Isabella Purba (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to develop a student digital worksheet product with a valid, practical, and effective model of Logan Avenue Problem Solving (LAPS)-Heuristic . Using the ADDIE model, results show the worksheet enhances critical thinking skills. The validity obtained from the material expert is 92% and based on the media expert is 85.4%. Also, the percentage of practicality is 92.9% and is included in the practical category. Implementation of learning with the application of student digital worksheets Effectiveness was demonstrated with 86.67% of students meeting learning completeness, and a medium improvement in critical thinking skills (gain score: 0.639). From the collected data, it is concluded that the Logan Avenue Problem Solving (LAPS)-Heuristic learning model developed meets the qualifications of valid, practical, and effective.